How the specifics of blockchain startups and their funding influence their lifecycle - Havelková, Barbora (2019)
Within the novel environment of blockchain-enabled fundraising, this thesis aims to extend the ICO literature by focusing on the post-ICO performance of the projects that get funded through a token sale. In the first part, the main specifics of this funding method were identified: lack of regulatory framework, unique technology utilization and a broad investor base. These specifics have the potential to be both beneficial and challenging in influencing the performance of start-ups funded via a token sale. To gain insight into how exactly they affect the success of the start-ups, a dataset of three hundred projects from the past four years was collected. In the scope of the empirical part, these projects were analyzed through regression models. In conclusion, the results suggested that this form of funding is more suited for projects that utilize blockchain in their own business models. It also facilitates funding of open source projects and projects in an early stage; however, the stage of the project should be carefully considered as it impacts the performance to a great extent. These and further findings from the empirical part can serve as a guide for entrepreneurs that consider blockchain-enabled funding to raise funds for their projects.